Unraveling the mechanism of flower color variation in Brassica napus by integrated metabolome and transcriptome analyses - Cui, Cheng; Zhang, Ka; Chai, Liang; Zheng, Benchuan; Zhang, Jinfang; Jiang, Jun; Tan, Chen; Li, Haojie; Chen, Daozong; Jiang, Liangcai (Frontiers in Plant Science, 2024)
Brassica napus is one of the most important oil crops in the world. Breeding oilseed rape with colorful flowers can greatly enhance the ornamental value of B. napus and thus improve the economic benefits of planting. As water-soluble flavonoid secondary metabolites, anthocyanins are very important for the synthesis and accumulation of pigments in the petals of plants, giving them a wide range of bright colors. Despite the documentation of over 60 distinct flower shades in B. napus, the intricacies underlying flower color variation remain elusive. Particularly, the mechanisms driving color development across varying flower color backgrounds necessitate further comprehensive investigation. This research undertook a comprehensive exploration through the integration of transcriptome and metabolome analyses to pinpoint pivotal genes and metabolites underpinning an array of flower colors, including beige, beige-red, yellow, orange-red, deep orange-red, white, light-purple, and purple. First, we used a two-way BLAST search to find 275 genes in the reference genome of B. napus Darmor v10 that were involved in making anthocyanins. The subsequent scrutiny of RNA-seq outcomes underscored notable upregulation in the structural genes F3H and UGT, alongside the MYB75, GL3, and TTG1 transcriptional regulators within petals, showing anthocyanin accumulation. By synergizing this data with a weighted gene co-expression network analysis, we identified CHS, F3H, MYB75, MYB12, and MYB111 as the key players driving anthocyanin synthesis in beige-red, orange-red, deep orange-red, light-purple, and purple petals. By integrating transcriptome and weighted gene co-expression network analysis findings with anthocyanin metabolism data, it is hypothesized that the upregulation of MYB75, which, in turn, enhances F3H expression, plays a pivotal role in the development of pigmented oilseed rape flowers. These findings help to understand the transcriptional regulation of anthocyanin biosynthesis in B. napus and provide valuable genetic resources for breeding B. napus varieties with novel flower colors.